Proposal For a Global Conceptual Model of University Missions in Light of The Literature - Yasmine LEBBADI; Mostafa ABAKOUY (Communications of International Proceedings, 2023)
The university is at the heart of every economy and country. Its traditional missions, namely scientific research, education, and professional integration, do not seem to best meet the needs of stakeholders, as this research will demonstrate. Indeed, clearly defining the missions of the university is a crucial and indispensable step in the processes of evaluation and development. The purpose of our article is therefore to construct a conceptual model of university missions based on a comprehensive and up-to-date literature review that highlights the academic, social, and economic missions of the university. This is intended to contribute to the literature with a new perspective and to provide universities with a trajectory to follow and a comprehensive view of their performance and development prospects.
Keywords: University; education; research; socio-economic engagement